THE POLYVINYLPYRROLIDONE CONTENT CONTROL IN DRUGS AND BIOLIQUIDS - Chmilenko, F.A.; Sapa, Yu.S.; Chmilenko, T.S.; Kharun, M.V. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
The spectrophotometric method of determination of polyvinylpyrrolidone (PVP) with using of organic dyes brilliant yellow (BY) and bromophenol blue (BPB) is elaborated for the content control of PVP in medicinal object. The method has been tasted for determination of PVP in Haemodesum - N and also in urine. The error of determination is less than 4%.